The social perspective of euthanasia in Spain: variables that predict attitudes towards euthanasia - Montañés Muro, Pilar; Soriano, Mª Eugenia; Manzano-García, Guadalupe (Anales de Psicología / Annals of Psychology, 2023)
The debate surrounding whether or not euthanasia should be a legal practice has been present in Spanish society since the 90’s. Recently, the Spanish government has passed Organic Law 3/2021 on the regulation of euthanasia. In relation to this question, which has raised and continues to raise controversy among both public opinion and the political and legal world, this work explores the relation of the different variables to the attitudes of the Spanish public towards euthanasia. For this purpose, 182 people residing in Spain took part in the study. The results indicate that there are no differences with regard to the age or gender of the participants in their attitudes towards euthanasia. Those who hold religious beliefs (irrespective of their religion) hold less favourable attitudes towards euthanasia than non-believers. Political orientation also relates to attitudes towards euthanasia. Finally, trust in the country’s health system and people’s empathic concern is also related to their attitudes towards euthanasia. At this point in time, when euthanasia has only just been regulated and starts to be put into practice in this country, it is of vital importance to consider the social perspective of euthanasia.